Global Financial Stability Report, April 2008 : Containing Systemic Risks and Restoring Financial Soundness. (Global Financial Stability Report; Global Financial Stability Report ;, 2008)
The events of the past six months have demonstrated the fragility of the global financial system and raised fundamental questions about the effectiveness of the response by private and public sector institutions. The report assesses the vulnerabilities that the system is facing and offers tentative conclusions and policy lessons. The report reflects information available up to March 21, 2008.